Microwave dielectric and attenuation properties of Ni0.7-xCoxZn0.3Fe2O4 thick films - Rendale, M. K.; Kulkarni, S. D.; Puri, Vijaya (Microelectronics International, 2009)
Purpose - The aim of this paper is to investigate permittivity of nano structured Ni0.7-xCoxZn0.3Fe2O4 thick films at microwave frequencies. Design/methodology/approach - Nanosized Ni0.7-xCoxZn0.3Fe2O4 ferrites with x = 0, 0.04, 0.08 and 0.12 were prepared by sucrose precursor technique using the constituent metal nitrates. Thick films of the ferrites were fabricated on alumina substrates by screen-printing technique. Microwave dielectric constant (epsilon') and the loss factor (epsilon `') for the thick films were measured by VSWR slotted section method in the 8-18 GHz range of frequencies. Microwave attenuation properties were studied using a waveguide reflectometer set up. Findings - Both the epsilon' and epsilon `' were found to vary with frequency and composition x It is observed that, value of epsilon' increases with increase in x, due to the increase in bulk density and reduction in porosity of the material, that resulted due to the substitution of cobalt in Ni-Zn ferrite. The microwave transmission loss offered by the thick films was found to increase with the increase in cobalt concentration x Within the band width of 4 GHz (from 12-16 GHz), all the films except that with x = 0.04 offered the reflection loss of less than 3 dB. Originality/value - The dielectric constant of Ni0.7-xCoxZn0.3Fe2O4 thick films have been reported for the first time. These thick films provide scope for cost effective planar ferrite devices.
Keywords: Microwaves; Oxides; Thick-film circuits

Influence of Mg2+ substitution on the magnetic and electrical properties of Li-Zn ferrite thick films synthesized with PVA matrix - Rendale, M. K.; Kulkarni, S. D.; Kulkarni, D. C.; Puri, Vijaya (Microelectronics International, 2011)
Purpose - The purpose of this paper is to investigate the effect of Mg2+ substitution on the magnetic and electrical properties of Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 thick films synthesized with polyvinyl alcohol (PVA) matrix. Design/methodology/approach - The nanoferrites Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) were synthesized by chemical technique using aqueous solution of PVA (the matrix) and thick films were fabricated by screen printing technique. The DC magnetic hysteresis measurements, AC magnetic susceptibility and DC electrical resistivity were measured as a function of temperature. Findings - The lattice parameter of thick film Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) increases with the substitution of Mg2+ ions for Li1+ and Fe3+. The surface morphology of the thick films showed the grain size increasing with Mg2+ substitution till x = 0.21 and then decreasing for the higher concentrations of magnesium. The magnetic moment n(B) (mu(B)) computed from the M-s obtained by extrapolation of the magnetization curve showed a gradual decrease with the composition till x = 0.21, beyond which a sudden decrease was observed. The resistivity of the films at room temperature had variation with composition x, similar to that of magnetic moment. The activation energies Delta E-F and Delta E-P were found to vary with composition x of the ferrite system. Originality/value - The paper reports, for the first time, the magnetic and electrical properties of fritless Li0.35-xMg2xZn0.3Fe2.35-xO4 thick films using PVA polymer matrix. Up to x = 0.21 (Mg2+), grain size increases and Curie temperature decreases beyond which reverse effect takes place.
Keywords: Alternating current; Direct current; Electrical properties; Films (states of matter); Magnetic moments